Papillon-Lefevre syndrome: A report of two cases - Rathod Varsha; Joshi Nilesh (Wolters Kluwer Medknow Publications, 2010)
Papillon-Lefevre syndrome is a rare (1-4 cases per million) autosomal recessive disorder showing predominantly oral and dermatological manifestations in the form of aggressive periodontitis affecting both primary and permanent dentition and palmoplantar hyperkeratosis. Genetic studies have shown that mutations in the major gene locus of chromosome 11q14 with loss of function of cathepsin C gene are responsible for Papillon-Lefevre syndrome. This report presents two siblings with classic signs and symptoms of Papillon-Lefevre syndrome. The exact cause for periodontal destruction in patients with Papillon-Lefevre syndrome is not known but it is thought to be due to defect in neutrophil function, immune suppression and mutations in cathepsin C gene.